Aryl-hydrocarbon receptor-dependent pathway and toxic effects of TCDD in humans: a population-based study in Seveso, Italy - Baccarelli, Andrea; Pesatori, Angela C; Masten, Scott A; Patterson, Donald G; Needham, Larry L; Mocarelli, Paolo; Caporaso, Neil E; Consonni, Dario; Grassman, Jean A; Bertazzi, Pier Alberto; Landi, Maria Teresa (Toxicology letters, 2004)
Approximately 20 years after the Seveso, Italy accident, we conducted a population-based study to evaluate the impact of 2,3,7,8-tetrachlorodibenzo- p-dioxin (TCDD) exposure upon immune and mechanistically based biomarkers of dioxin response in humans. TCDD toxic effects are known to be mediated by the aryl-hydrocarbon receptor (AhR). We randomly selected 62 study subjects from the highest exposed zones and 59 from the surrounding non-contaminated area. Current lipid-adjusted plasma TCDD concentrations in these subjects ranged from 3.5 to 90 ng/kg (or ppt) and were negatively associated with plasma IgG concentrations ( r=−0.35; P=0.0002). The expression of genes in the AhR-dependent pathway, including AhR, aryl-hydrocarbon receptor nuclear translocator (ARNT), CYP1A1, and CYP1B1 transcripts, and the CYP1A1-associated 7-ethoxyresorufin- O-deethylase (EROD) activity was measured in lymphocytes. AhR mRNA levels in uncultured lymphocytes were negatively associated with plasma TCDD ( P=0.03). When mitogen-induced lymphocytes were cultured with 10 nM TCDD, all AhR-dependent genes were induced 1.2- to 13-fold. In these cells, plasma TCDD was associated with decreased EROD activity. Markers within the AhR pathway were correlated with one another. Our findings suggest the presence of long-term effects in the subjects exposed to TCDD after the Seveso accident.